The translation of Chinua Achebe's Things fall apart into isiXhosa Lwadilik'udonga : a critical analysis - Ntwana, Thenjiswa (Stellenbosch : Stellenbosch University, 2012)
Thesis (MPhil)--Stellenbosch University, 2005.